Pathological and immunohistochemical study of lethal primary brain stem injuries - Rongchao Sun; Shudong Yang; Zhiyi Zhou (BMC, 2012)
Abstract Background Many of the deaths that occur shortly after injury or in hospitals are caused by mild trauma. Slight morphological changes are often found in the brain stems of these patients during autopsy. The purpose of this study is to investigate the histopathological changes involved in primary brain stem injuries (PBSI) and their diagnostic significance. Methods A total of 65 patients who had died of PBSI and other conditions were randomly selected. They were divided into 2 groups, an injury group (25 cases) and a control group (20 cases). Slides of each patient's midbrain, pons, and medulla oblongata were prepared and stained with HE, argentaffin, and immunohistochemical agents (GFAP, NF, amyloid-ß, MBP). Under low power (×100) and NF staining, the diameter of the thickest longitudinal axon was measured at its widest point. Ten such diameters were collected for each part of the brain (midbrain, pons, and medulla oblongata). Data were recorded and analyzed statistically. Results Brain stem contusions, astrocyte activity, edema, and pathological changes in the neurons were visibly different in the injury and control groups (P < 0.05). Characteristic changes occurred in the neural axons, axon diameter varied from axon to axon and even over different segments of one axon, and several pathological phenomena were observed. These included segmental thickening and curving, wave-like processing, disarrangement, and irregular swelling. A few axons ruptured and intumesced into retraction balls. Immunohistochemical MBP staining showed enlargement and curving of spaces between the myelin sheaths and axons in certain areas. The myelin sheaths lining the surfaces of the axons were in some cases incomplete and even exfoliated, and segmentation disappeared. These pathological changes increased in severity over time (P < 0.05). Conclusions These histopathological changes may prove beneficial to the pathological diagnosis of PBSI during autopsy. The measurement of axon diameters provides a referent quantitative index for the diagnosis of the specific causes of death involved in PBSI. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1345298818712204